International register “Dynamics analysis of comorbidities in SARS-CoV-2 survivors” (AKTIV SARS-CoV-2): analysis of predictors of short-term adverse outcomes in COVID-19 - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; Y. N. Belenkov; A. O. Konradi; Y. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; H. G. Hayrapetyan; A. P. Babin; I. G. Bakulin; et al. (Российский кардиологический журнал, 2021)
The international AKTIV register presents a detailed description of out- and inpatients with COVID-19 in the Eurasian region. It was found that hospitalized patients had more comorbidities. In addition, these patients were older and there were more men than among outpatients. Among the traditional risk factors, obesity and hypertension had a significant negative effect on prognosis, which was more significant for patients 60 years of age and older. Among comorbidities, CVDs had the maximum negative effect on prognosis, and this effect was more significant for patients 60 years of age and older. Among other comorbidities, type 2 and 1 diabetes, chronic kidney disease, chronic obstructive pulmonary disease, cancer and anemia had a negative impact on the prognosis. This effect was also more significant (with the exception of type 1 diabetes) for patients 60 years and older. The death risk in patients with COVID-19 depended on the severity and type of multimorbidity. Clusters of diseases typical for deceased patients were identified and their impact on prognosis was determined. The most unfavorable was a cluster of 4 diseases, including hypertension, coronary artery disease, heart failure, and diabetes mellitus. The data obtained should be taken into account when planning measures for prevention (vaccination priority groups), treatment and rehabilitation of COVID-19 survivors.